1987
DOI: 10.1159/000457755
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Thiopental Pharmacokinetics in Brain-Injured Children and Neonates

Abstract: High-dose thiopental was administered in 8 children with uncontrollable seizures or hypoxic encephalopathy (group A) and 7 full-term neonates with neonatal asphyxia (group B), All of them were submitted to artificial hyperventilation to maintain pCO(2) near 3.5 kPa. Rectal temperature was kept at about 35 °C. Thiopental was infused with a rate of 2-4 mg^-1-kg^-1, with treatment lasting 32-192 h for group A (mean 103 h), and 36-48 h for group B (mean 38.5 h). Plasma concentration-time data were analysed pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…However, in 2003, another study on WHS showed that neonates aged between 1 day and <1 month had tonicclonic seizures and were treated with phenobarbital. 8 Thus, seizure onset in WHS can occur in the neonatal period; however, to our knowledge, this is the first case report on early postnatal seizures in a neonate with WHS.…”
Section: Discussionmentioning
confidence: 81%
“…However, in 2003, another study on WHS showed that neonates aged between 1 day and <1 month had tonicclonic seizures and were treated with phenobarbital. 8 Thus, seizure onset in WHS can occur in the neonatal period; however, to our knowledge, this is the first case report on early postnatal seizures in a neonate with WHS.…”
Section: Discussionmentioning
confidence: 81%
“…The low total administered thiopental dose and the different schedule compared to previous reports concerning thiopental utilization in neonates [15,16] and children [17] (10-15 mg/kg loading dose followed by a maintain ing infusion of 0.75-5 mg/g/h) avoid the major side effects (severe hypotension and quicker and shorter lasting, so that, if necespharmacodynamic tolerance) related to this sary, it can be administered again (as de scribed here for 1 newborn) with less risk of…”
Section: Discussionmentioning
confidence: 92%
“…Like pentobarbital, thiopental is a suitable agent for patients with raised intracranial pressure. PK and PD studies have been rarely performed in children, and most of them date from the 1980s . Despite a reported double clearance compared to adults, doses do not need to be doubled .…”
Section: Pharmacological Agentsmentioning
confidence: 99%